Light-intensity-dependent regulatory mechanisms in protection of Photosystem I in Arabidopsis - Rantala, Sanna (fi=Turun yliopisto|en=University of Turku|, 2019)
In photosynthetic light reactions, photosystem (PS)II and PSI as well as Cytochrome b6f, which are embedded in the thylakoid membrane of chloroplasts, transfer electrons from water molecules to NADP+ using the light energy collected mostly by light harvesting complexes (LHC)II and LHCI. Simultaneously, an electrochemical gradient is formed across the thylakoid membrane and utilized by ATP synthase to catalyse the synthesis of ATP. With the end products of photosynthetic light reactions, NADPH and ATP, plants bind atmospheric carbon dioxide into organic compounds, which not only support the plants’ growth and development but also nearly all heterotrophic life on Earth. The flow of electrons in the photosynthetic machinery needs to be strictly controlled in order to avoid damage to PSI that, unlike PSII, lacks an efficient repair cycle. To protect PSI, plants are able to control the distribution of energy between the photosystems through phosphorylating and dephosphorylating LHCII, to optimize the electron transfer rate from PSII to PSI through PGR5 protein and to cycle electrons from PSI back to the electron transfer chain through the NDH-1 complex. Here, I applied several biochemical and biophysical approaches to compare the thale cress Arabidopsis thaliana wild type and transgenic lines lacking certain regulatory proteins. I showed that dephosphorylation of LHCII protects PSI from excess electrons by physically separating the complexes but also by regulating the location of Cytochrome b6f and ATP synthase in the thylakoid membrane. Furthermore, I showed that the activation of PGR5 requires light and that when active, the protein controls electron transfer from PSII to PSI but not from PSI onwards. Finally, I demonstrated that in the case of PSI damage, both PGR5 and NDH-1 participate in maintaining the function of the photosynthetic electron transfer chain.

Fotosynteesin valoreaktioissa viherhiukkasen tylakoidikalvoon sitoutuneet fotosysteemi (PS)II ja PSI sekä Sytokromi b6f siirtävät elektroneja vesimolekyyliltä NADP+:lle pääasiassa valohaavikompleksien (LHC)II ja LHCI keräämän valoenergian avulla. Samalla tylakoidikalvolle muodostuu elektrokemiallinen gradientti, jonka avulla ATP-syntaasi katalysoi ATP:n muodostumista. Valoreaktioiden lopputuotteita, NADPH:ta ja ATP:ta, kasvi käyttää sitoakseen ilmakehän hiilidioksidia eloperäisiksi yhdisteiksi, jotka ylläpitävät paitsi kasvien kasvua ja kehitystä, myös lähes kaikkea Maan toisenvaraista elämää. Elektronien kulkua valoreaktioissa on ohjattava tarkoin, jotteivät ne vaurioita PSI:tä, jota varten ei ole kehittynyt tehokasta korjauskiertoa kuten PSII:lla. PSI:n suojaamiseksi kasvit kykenevät säätelemään valoenergian jakautumista fotosysteemien välillä fosforyloimalla ja defosforyloimalla LHCII:ta, optimoimaan elektronien kulkunopeutta PSII:lta PSI:lle PGR5-proteiinin avulla sekä kierrättämään elektroneja PSI:ltä takaisin elektroninsiirtoketjuun NDH-1-kompleksin kautta. Tässä väitöskirjaprojektissa vertailin biokemiallisin ja biofysikaalisin menetelmin lituruohon Arabidopsis thaliana villityyppiä ja mutanttilinjoja, joilta on poistettu tunnettu säätelyproteiini. Osoitin, että LHCII:n defosforylaatio suojaa kirkkaassa valossa PSI:tä liiallisilta elektroneilta erottamalla kompleksit fyysisesti toisistaan, mutta säätelee myös Sytokromi b6f:n ja ATP-syntaasin sijaintia tylakoidikalvolla. Osoitin myös, että PGR5-proteiini aktivoituu valossa ja kontrolloi elektroninsiirtoa PSII:lta PSI:lle, mutta ei PSI:ltä eteenpäin. Lisäksi havainnollistin, että mikäli PSI kuitenkin vahingoittuu, sekä PGR5 että NDH-1 osallistuvat fotosynteettisen elektroninsiirtoketjun toiminnan säilyttämiseen.